Self-Esteem dengan Self-Presentation Unggahan Selfie Instagram pada Mahasiswi : Syifa Nur Baity, Timorora Sandha Perdhana - Nur Baity, Syifa; Sandha Perdhana, Timorora (Fakultas Psikologi Universitas Bhayangkara Jakarta Raya, 2023)
Selfie is the activity of taking pictures using a mobile phone camera that displays all or part of the user's body, uploading selfies to Instagram can make users believe in becoming famous. Self-esteem and self-presentation are important links in selfie uploads, with individual self-presentations can make a good impression on other individuals. Self-Esteem is formed from the interaction of an individual with another individual. This study aims to determine the Relationship Between Self-Esteem and Self-Presentation of Instagram Selfie Uploads at Bhayangkara University Students, Greater Jakarta. The researchers used a quantitative method with a correlational approach, namely the spearman's rho correlation technique, and used 105 subjects, namely students of Bhayangkara University, Greater Jakarta. The results of this study show that the value of the correlation coefficient of 0.198* with its significance level is (p) of < 0.001 which shows significant results (p) < 0.05 which means that there is a relationship between self-esteem and self-presentation of Instagram selfie uploads at Bhayangkara University students, Greater Jakarta with a positive research direction, which if the higher the self-esteem then the higher the self-presentation and vice versa. As for suggestions for researchers, they can then examine other factors that have a relationship with the self-presentation of female students on Instagram social media such as body image factors and popularity factors.